Reduction of Ship Resistance using EPPLER 874 Foil - เอี่ยมพรสิน ฉัตรชัย; กันเนื่อง วลีพรรณ; หนูสมตน จารุพันธุ์ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2022)
The purpose of this research is to reduce ship resistance of the boat by using hydrofoils under the hull. The geometric similarity theory was applied to design a model with a dimension ratio of 3.2. The model boat was built to confirm that when it was extended by this dimension ratio, the hydrofoil could provide a higher lift force than the actual load. The experiment results of the model on three types of hydrofoil; EPPLER874, NACA63209, and NACA4412; showed that EPPLER874 with the attack angle of 12o provided the best model speed. Therefore, EPPLER874 foil was selected to build the hydrofoil boat. The overall load of the boat with hydrofoil is 260 kg. EPPLER874 hydrofoils made of fiberglass. The bow foil is V-shape with the chord length of 0.2 m. The stern foil is trapezoid-shaped with the chord length of 0.3 m. The experiment results have shown that 12o of hydrofoil attack angle maintains the stable lift force when moving forward and turning circle. In the comparison of the EPPLER874 hydrofoil boat with the non-foil boat, it has been found that the speed of the hydrofoil boat increased by 15.65%, whereas the fuel consumption is reduced by 48.37%.